Western-Type Communications Research in the Third World - John Lent (Communicare)
RESPONDING to the complaint that a great deal of the communications research in the Third World is Western-biased, this article, using sources and examples from many parts of the world, looks at the past, present and future of social science research as applied to mass communications. Among complaints have been that the research grew up promoting business-industrial and military-psychological warfare aims (mainly of entities in the United States), and pushing for the status quo and homogenization of cultures. Much of the research was ethnocentric, myopic, culture- and timebound. To avoid some of these problems, cross- cultural and cross-national research should seek to determine equivalence levels (functional, conceptual, linguistic and metric): relevance and worth of the research, especially to the country being studied: and degree and type of methodology.